SmartRoadSense (SRS) Il crowd-sensing per monitorare il fondo stradale. Sinergie di ricerca dalla geomatica al mapping, dai sensori alla statistica. - Santarsiero, Domenico (GEOmedia, 2015)
GEOmedia interview the project leader SmartRoadSense (SRS) Alessandro Bogliolo. SmartRoadSense (SRS) is the crowdsensing to monitor the road surface. Research synergies from geomatics to mapping, from sensors to statistics.